Assessment of Soybean Meal as Dietary Fishmeal Replacement in Red Sea Bream (Pagrus Major) Juveniles Based on Energy Budget Analysis - Sumule, Ophirtus; Sudaryono, Agung; Ishikawa, Manabu; Koshio, Shunsuke (Indonesian Aquaculture Society (MAI), 2017)
The effects of soybean meal (SBM) on the energy budget of red sea bream Pagrus major juveniles (3.2 g initial wet weight) were determined by supplementing SBM in the diet at 0% (control diet), 16%, 24%, 32% and 39%, with the fishmeal content correspondingly reduced from 55% to 29%. Diets were made isoenergetic and isonitrogenous by changing the lipid and carbohydrate levels. Fish were fed to apparent satiation for 30 days in duplicates per diet (20 fish per replicate). Ammonia excretion and oxygen consumption were continuously measured during the growth trial, whereas digestibility after the termination of growth trial. Feed intake, body weight gain, and specific growth rate of fish increased to a peak at 24% SBM level, which again decreased as the SBM level was further increased. The apparent digestibility of energy was similar in all dietary treatments, while the digestible of dry matter increased with the SBM level. A lower proportion of energy intake as growth at 39% SBM level was attributed to the higher energy intake channeled to fecal ammonia. This study suggested that the inclusion level of SBM in diets for red sea bream juveniles should be is optimal at the inclusion range 24–32%, thus correspondingly replacing the fishmeal content by 24–32%.